The Asian Financial Crisis: Lessons from Thailand - Jacque, Laurent (Tufts Archival Research Center, 2005)
Volume 23, Issue 1. Winter/Spring The origin of the crisis lies in the private sector, which misallocated financial resources with government approval. Inappropriate Western-style policies-aimed to improve economic conditions--only worsened the situation.